2021
DOI: 10.3390/brainsci11091184
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Adult Patients with 5q-Associated Spinal Muscular Atrophy

Abstract: In previous studies, a below-average, average, or above-average intelligence quotient (IQ) in children with SMA was detected but, aside from a severe physical disability, the cognitive performance of adult SMA patients has not yet been evaluated. The intelligence test used in this study, the Wechsler Adult Intelligence Scale, fourth edition (WAIS-IV), was used to measure major intelligence components of adult SMA patients. The WAIS-IV determines four index scores representing verbal comprehension, perceptual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…Recent comparative studies with ALS patients and controls have reported no considerable cognitive impairment in adult patients with SMA [ 9 , 10 ]. However, a trend towards lower cognitive performance in comparison to healthy controls was supposed, emphasizing SMA as a multi-systemic disorder [ 11 ]. Yet, there is little information about the effect of nusinersen on neuropsychological functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent comparative studies with ALS patients and controls have reported no considerable cognitive impairment in adult patients with SMA [ 9 , 10 ]. However, a trend towards lower cognitive performance in comparison to healthy controls was supposed, emphasizing SMA as a multi-systemic disorder [ 11 ]. Yet, there is little information about the effect of nusinersen on neuropsychological functions.…”
Section: Discussionmentioning
confidence: 99%
“…However, executive function inversely correlated with motor function, suggesting a compensation to physical restrictions in SMA [ 10 ]. In contrast, lower IQ index scores were found for working memory and perceptual reasoning in patients with SMA type 2 than in general population, encouraging SMA as a multi-systemic disease and disapproving the hypothesis of improved cognitive skills as a compensation for physical impairment [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, similar to ALS, SMA exhibits SMN protein deficiency on the pathogenetic molecular pathway that is thought to play a crucial role in brain development (38). In a study by Kizina et al the Wechsler Adult Intelligence Scale (Fourth edition), an internationally recognized and validated intelligence quotient (IQ) test, was used to measure major intelligence components of adult SMA patients (10). In their study, SMA type III patients showed a trend of lower IQ scores.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar to Amyotrophic Lateral Sclerosis (ALS), which is characterized by a progressive deterioration and neurodegeneration of motor neurons, patients with SMA may also have cognitive deficits. Recent studies reported that the cognitive performance of SMA patients was below average (10,11). Although SMA is widely known as a spinal motor neuron disease, recent evidence has indicated that it is a multiorgan disease with disease involvement of several non-motor regions (12).…”
Section: Introductionmentioning
confidence: 99%
“…Existing data show that a reduction of SMNprotein does not have a severe effect on the development of cognitive function in adults with SMA. Nevertheless, the mean intelligence quotient (IQ) in SMA patients has been contradictorily described as above [33] or below average compared to healthy subjects [15,17,28].…”
Section: Introductionmentioning
confidence: 99%